Stimulating Creativity: Examining the Effectiveness of Four Cognitive‐based Creativity Training Techniques. (25th January 2022) - Gu, Xiaojing; Ritter, Simone M.; Delfmann, Lea R.; Dijksterhuis, Ap
Abstract: Creative thinking is needed to thrive in our fast‐changing world. It has been shown that creative thinking skills can be enhanced through training. Whereas previous research has mainly focused on examining the overall effectiveness of comprehensive creativity training programs, this study examined the effectiveness of four cognitive‐based training techniques (SCAMPER, random connection, schema violation, and simple ideation), each with the aim of training specific cognitive processes underlying creativity. The effectiveness of the four techniques was tested using a pre–posttest between‐subjects design. The participants were assigned to one of the four creativity training conditions or a control condition and practiced each training technique for approximately 20 min. Before and after training, the participants' creative performance was measured with divergent thinking (Alternative Uses Task; fluency, flexibility, originality, creativity, usefulness) and convergent thinking (Remote Associates Test) tasks. The results showed marginal to significant improvements on several key indicators of divergent thinking, but none of the techniques led to improvement in convergent thinking. Specifically, the SCAMPER technique targeting conceptual expansion marginally improved idea originality, while the random connection technique targeting conceptual combination and the schema violation technique targeting cognitive flexibility seemed to facilitate idea fluency and idea flexibility. No improvement was observed for the simple ideation technique and the control condition.